Issues and challenges in achievement of sustainable development goals for microfinance - Abdul Razak, Dzuljastri (2019)
Sustainable Development Goals (SDGs) is a set of goals which was build upon the Millennium Development Goals (MDGs) They are one of the main outcomes of Rio +20 conference, aimed to be achieved by 2030. There are total of 17 SDGs goals. Some of the important aspect of this are the eradication of poverty, economic growth, and reduce inequalities. This objective of this study is to investigate four (4) microfinance models practices in Bangladesh, Malaysia, Indonesia, and Pakistan to find out whether their practices meet the three SDGs goals mentioned. The methodology of this research is carried out by means of library search and content analysis on operations of the four models and the extent they meet the objectives ofMaqasid Al-Shariah.The findings of this study would contribute towards the development of the microfinance sector which is a very important component in driving country’s economy.